Transfer of Rights to Land And Buildings with A Binding Sale And Purchase Agreement Reviewed From SEMA No 4 of 2016 - Renny Yuliyanti; Fitria Dewi Navisa (Journal of Law, Politic and Humanities, 2025)
The transfer of land and/or building rights through a sale and purchase agreement, as stipulated in the Circular Letter of the Supreme Court Number 4 of 2016, is valid without necessitating a deed of sale and purchase, in accordance with Article 1338 of the Civil Code, while the deed constitutes an authentic deed per Article 1868 of the Civil Code. Nonetheless, it does not ensure that the conveyance of land rights to another individual may be substantiated unless the transfer is executed in accordance with Article 1459 of the Civil Code; a PPJB prior to an AJB is permissible provided that the required requirements in the regulation are satisfied. The legal protection acquired by the parties in the transfer of land and/or building rights through PPJB is preventive in nature. This is achieved by including specific clauses in the PPJB that ensure legal protection for the parties involved, thereby facilitating realization and safeguarding their interests. Repressive legal protection for the parties can be addressed by alternatives to judicial and court institutions